Preparation method of high-dispersion white carbon black and application of high-dispersion white carbon black in reinforcing green tire
By adopting a technical solution of synergistic modification of phenyltrimethoxysilane and vinyltrimethoxysilane, the number of hydroxyl groups on the surface of white carbon black is reduced, and its dispersion and mechanical properties in the rubber matrix are improved, which solves the problem of poor dispersion of white carbon black, and achieves high dispersion, strong low temperature flexibility and high anti-slip effects.
Patent Information
- Application Number
- CN202411526060.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The dispersion of white carbon black in the rubber matrix is poor, resulting in poor compatibility when combined with rubber, poor mechanical properties of the rubber, easy adsorption accelerator and anti-aging agent, reducing the vulcanization rate.
Using a technical solution for synergistic modification of phenyltrimethoxysilane and vinyltrimethoxysilane, by adding silica wet gel, deionized water and silane coupling agent vinyltrimethoxysilane (A171) to the reactor, heating and adjusting the pH value, pre-hydrolyzed phenyltrimethoxysilane (PTMS) is added for the modification reaction, reducing the number of hydroxyl groups on the surface of white carbon black, and improving activation and lipophilization.
The dispersion of white carbon black in the rubber matrix is significantly improved, mechanical properties and dynamic mechanical properties are improved, and the purposes of high dispersion, strong low temperature flexibility and high anti-slip are achieved.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of white carbon black preparation, and specifically relates to a method for preparing highly dispersed white carbon black and an application thereof in reinforcing green tires. Background Art
[0002] White carbon black, also known as hydrated silicon dioxide (SiO2·nH2O), is in the form of white powder or granules, non-toxic, stable in nature, resistant to high temperatures and electrically insulating. White carbon black, as a reinforcing agent, is used in the field of tire rubber to reduce rolling resistance, save energy and reduce consumption, and is one of the ideal raw materials for "green tires". However, the surface of white carbon black contains a large number of silanol groups, which have high activity, making white carbon black hydrophilic, poorly dispersible, and easy to agglomerate, resulting in poor compatibility at the rubber matrix-white carbon black interface when combined with rubber, poor mechanical properties of the rubber compound, easy adsorption of accelerators and anti-aging agents, and reduced vulcanization speed. Therefore, silane coupling agents are often used to modify and optimize its surface properties. It is mainly to use the silanol groups generated by the hydrolysis of silane coupling agents to condense with the silanol groups on the surface of white carbon black particles to reduce the number of surface silanol groups and improve the dispersibility of white carbon black in tire rubber. However, there are many factors that affect the modification effect, such as the alkyl group of the silane coupling agent, especially the modification conditions, because the hydrolyzed hydroxyl groups of the silane coupling agent itself also have self-condensation, thus affecting the performance after modification. Research on the modification of silica to improve its dispersibility in tire rubber, enhance processing performance, save energy and reduce consumption, and improve the tire's anti-skid performance is a hot topic in the industry. Summary of the invention
[0003] In order to solve the above technical problems, the purpose of the present invention is to provide a method for preparing highly dispersed and highly low-temperature flexible white carbon black for reinforcing green tires. Compared with traditional white carbon black, the white carbon black prepared by this method has a greatly reduced number of surface hydroxyl groups, improved activation and lipophilicity, and enhanced hydrophobicity; when applied to styrene-butadiene rubber, it significantly improves tire processing performance, improves its dispersibility in the rubber material, and also improves mechanical properties and dynamic mechanical properties, thereby achieving the purpose of high dispersion, strong low-temperature flexibility and high wet-slip resistance.
[0004] Based on the above objectives, the present invention adopts a technical solution of synergistic modification of phenyltrimethoxysilane and vinyltrimethoxysilane.
[0005] Specifically, the present invention first provides a method for preparing highly dispersed white carbon black, comprising the following steps: adding a certain amount of wet silica gel, deionized water and a silane coupling agent vinyl trimethoxy silane (A171) into a reaction kettle, stirring and heating in an oil bath pot to a certain temperature, adjusting to a set pH value, and then adding a certain proportion of pre-hydrolyzed silane coupling agent phenyl trimethoxy silane (PTMS) for a certain period of time for modification reaction, washing with alcohol, filtering and drying after the reaction to obtain a highly dispersed and strong low-temperature flexible white carbon black for reinforcing green tires.
[0006] Among them, the total mass of the modifiers PTMS and A171 is 3.5%-17.5% of the mass of the SiO2 wet gel; the mass ratio of PTMS:A171 is 5:2; preferably, the total mass of the modifiers PTMS and A171 is 14%-17.5% of the mass of the SiO2 wet gel.
[0007] The mass ratio of the wet silica gel to deionized water is 2:1.
[0008] The modification temperature is 70-90°C, the modification time is 30-150 min, and the modification pH is 2.5-4.5; preferably, the modification temperature is 80°C, the modification time is 90 min, and the modification pH is 3.5.
[0009] The PTMS pre-hydrolysis solution is obtained by hydrolyzing PTMS in a solvent of anhydrous ethanol and water, the hydrolysis pH is 4.0, and the mass ratio of PTMS to anhydrous ethanol and water is 5:14:5.
[0010] The white carbon black prepared by the present invention has the following beneficial effects: compared with unmodified precipitated white carbon black and single modifier modified white carbon black, the number of surface hydroxyl groups is reduced, the hydrophobicity is improved, and the problem of poor dispersion of white carbon black in the rubber matrix is solved. The activation degree reaches 100%, the lipophilicity reaches 10.1%, and the number of surface hydroxyl groups is 0.924 / nm 2 .
[0011] The present invention also provides the use of the white carbon black prepared by the above method for reinforcing green tires, which has strong low-temperature flexibility and high wet-skid resistance.
[0012] Styrene-butadiene rubber (SBR) is a commonly used green tire tread rubber. When the white carbon black prepared by the present invention is applied to styrene-butadiene rubber, compared with the unmodified white carbon black reinforcement, due to the simultaneous grafting of benzene rings and unsaturated double bonds on the surface, it can participate in the vulcanization of the rubber, improve the crosslinking density of the rubber, and thus improve the reinforcement effect of white carbon black. The vulcanization time is reduced by 68.8%, the Mooney viscosity is reduced by 61.3%, and the processing difficulty is reduced; the tensile strength is increased by 14.0%, the elongation at break is increased by 11.3%, and the 300% and 500% elongation stresses are increased by 43.4% and 31.3%, respectively, which improves the mechanical properties. At the same time, the Payne effect is weakened, △G′ is reduced, its dispersibility in the rubber matrix is improved, tanδ (-10℃) and tanδ (0℃) are improved, and the shear compliance is greatly improved across the board. The dispersibility of the modified white carbon black in the rubber is improved, and greater viscous resistance and traction are obtained under normal low temperature conditions, which improves the low-temperature flexibility and anti-slip performance of the tread rubber. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 The shear storage modulus-strain curves of the rubber materials of Example 1 and Comparative Examples 1, 2, and 3 are shown;
[0014] Figure 2 The rubber loss factor-temperature curve of Example 1 and Comparative Examples 1, 2, and 3 is shown.
[0015] Figure 3 The shear compliance-temperature curve of the rubber materials of Example 1 and Comparative Examples 1, 2, and 3 are shown. DETAILED DESCRIPTION
[0016] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention in various other specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0017] The present invention is further described in detail below in conjunction with embodiments:
[0018] Example 1
[0019] 500 g SiO2 wet gel (855 MP, BET 180 m 2 / g) was added to the reactor, 250g of deionized water and A171 were added, and the temperature was raised to 80°C by stirring in an oil bath pot, and the modified pH was adjusted to 3.5, and then pre-hydrolyzed PTMS (phenyltrimethoxysilane pre-hydrolysis used ethanol solution as the hydrolysis solvent, wherein the mass of PTMS was 50g, ethanol and water were 140g and 50g respectively, and the hydrolysis pH value was 4.0), the total mass of PTMS+A171 was 70g, and the mass ratio of PTMS:A171 was 5:2 for modification, and the reaction time was 90min. After the reaction was completed, it was washed with alcohol, filtered and dried to obtain a highly dispersed and strong low-temperature flexible white carbon black for reinforcing green tires.
[0020] Example 2
[0021] 500g SiO2 wet gel was added to the reactor, 250g deionized water and A171 were added, and the temperature was raised to 80℃ by stirring in an oil bath, and the modified pH was adjusted to 3.5, and then pre-hydrolyzed PTMS (PTMS mass was 12.5g, ethanol and water were 35g and 12.5g, respectively, and the hydrolysis pH was 4.0) was added, the total mass of the modifier was 17.5g, and the mass ratio of PTMS: A171 was 5:2 for modification, and the reaction time was 90min. After the reaction was completed, it was washed with alcohol, filtered and dried to obtain a highly dispersed and strong low-temperature flexible white carbon black for reinforcing green tires.
[0022] Example 3
[0023] 500g SiO2 wet gel was added to the reactor, 250g deionized water and A171 were added, and the temperature was raised to 80℃ by stirring in an oil bath, and the modified pH was adjusted to 3.5, and then pre-hydrolyzed PTMS (PTMS mass was 25g, ethanol and water were 70g and 25g respectively, and the hydrolysis pH value was 4.0) was added, the total mass of the modifier was 35g, and the mass ratio of PTMS: A171 was 5:2 for modification, and the reaction time was 90min. After the reaction was completed, it was washed with alcohol, filtered and dried to obtain a highly dispersed and strong low-temperature flexible white carbon black for reinforcing green tires.
[0024] Example 4
[0025] 500g SiO2 wet gel was added to the reactor, 250g deionized water and A171 were added, and the temperature was raised to 80℃ by stirring in an oil bath, and the modified pH was adjusted to 3.5, and then pre-hydrolyzed PTMS (PTMS mass was 37.5g, ethanol and water were 105g and 37.5g, respectively, and the hydrolysis pH was 4.0) was added, the total mass of the modifier was 52.5g, and the mass ratio of PTMS: A171 was 5:2 for modification, and the reaction time was 90min. After the reaction was completed, it was washed with alcohol, filtered and dried to obtain a highly dispersed and strong low-temperature flexible white carbon black for reinforcing green tires.
[0026] Example 5
[0027] 500g SiO2 wet gel was added to the reactor, 250g deionized water and A171 were added, and the temperature was raised to 80℃ by stirring in an oil bath, and the modified pH was adjusted to 3.5, and then pre-hydrolyzed PTMS (PTMS mass was 62.5g, ethanol and water were 175g and 62.5g, respectively, and the hydrolysis pH value was 4.0) was added, the total mass of the modifier was 87.5g, and the mass ratio of PTMS: A171 was 5:2 for modification, and the reaction time was 90min. After the reaction was completed, it was washed with alcohol, filtered and dried to obtain a highly dispersed and strong low-temperature flexible white carbon black for reinforcing green tires.
[0028] Example 6
[0029] 500g SiO2 wet gel was added to the reactor, 250g deionized water and A171 were added, and the temperature was raised to 70℃ by stirring in an oil bath, and the modified pH was adjusted to 3.5, and then pre-hydrolyzed PTMS (PTMS mass was 25g, ethanol and water were 70g and 25g respectively, and the hydrolysis pH value was 4.0) was added, the total mass of the modifier was 35g, and the mass ratio of PTMS: A171 was 5:2 for modification, and the reaction time was 90min. After the reaction was completed, it was washed with alcohol, filtered and dried to obtain a highly dispersed and strong low-temperature flexible white carbon black for reinforcing green tires.
[0030] Example 7
[0031] 500g SiO2 wet gel was added to the reactor, 250g deionized water and A171 were added, and the temperature was raised to 90°C by stirring in an oil bath, and the modified pH was adjusted to 3.5, and then pre-hydrolyzed PTMS (PTMS mass was 25g, ethanol and water were 70g and 25g, respectively, and the hydrolysis pH value was 4.0) was added, the total mass of the modifier was 35g, and the mass ratio of PTMS: A171 was 5:2 for modification, and the reaction time was 90min. After the reaction was completed, it was washed with alcohol, filtered and dried to obtain a highly dispersed and strong low-temperature flexible white carbon black for reinforcing green tires.
[0032] Example 8
[0033] 500g SiO2 wet gel was added to the reactor, 250g deionized water and A171 were added, and the temperature was raised to 80℃ by stirring in an oil bath, and the modified pH was adjusted to 3.5, and then pre-hydrolyzed PTMS (PTMS mass was 25g, ethanol and water were 70g and 25g respectively, and the hydrolysis pH value was 4.0) was added, the total mass of the modifier was 35g, and the mass ratio of PTMS: A171 was 5:2 for modification, and the reaction time was 30min. After the reaction was completed, it was washed with alcohol, filtered and dried to obtain a highly dispersed and strong low-temperature flexible white carbon black for reinforcing green tires.
[0034] Example 9
[0035] 500g SiO2 wet gel was added to the reactor, 250g deionized water and A171 were added, and the temperature was raised to 80℃ by stirring in an oil bath, and the modified pH was adjusted to 3.5, and then pre-hydrolyzed PTMS (PTMS mass was 25g, ethanol and water were 70g and 25g respectively, and the hydrolysis pH value was 4.0) was added, the total mass of the modifier was 35g, and the mass ratio of PTMS: A171 was 5:2 for modification, and the reaction time was 150min. After the reaction was completed, it was washed with alcohol, filtered and dried to obtain a highly dispersed and strong low-temperature flexible white carbon black for reinforcing green tires.
[0036] Example 10
[0037] 500g SiO2 wet gel was added to the reactor, 250g deionized water and A171 were added, and the temperature was raised to 80℃ by stirring in an oil bath, and the modified pH was adjusted to 2.5, and then pre-hydrolyzed PTMS (PTMS mass was 25g, ethanol and water were 70g and 25g respectively, and the hydrolysis pH value was 4.0) was added, the total mass of the modifier was 35g, and the mass ratio of PTMS: A171 was 5:2 for modification, and the reaction time was 90min. After the reaction was completed, it was washed with alcohol, filtered and dried to obtain a highly dispersed and strong low-temperature flexible white carbon black for reinforcing green tires.
[0038] Embodiment 11
[0039] 500g SiO2 wet gel was added to the reactor, 250g deionized water and A171 were added, and the temperature was raised to 80℃ by stirring in an oil bath, and the modified pH was adjusted to 4.5, and then pre-hydrolyzed PTMS (PTMS mass was 25g, ethanol and water were 70g and 25g respectively, and the hydrolysis pH value was 4.0) was added, the total mass of the modifier was 35g, and the mass ratio of PTMS: A171 was 5:2 for modification, and the reaction time was 90min. After the reaction was completed, it was washed with alcohol, filtered and dried to obtain a highly dispersed and strong low-temperature flexible white carbon black for reinforcing green tires.
[0040] Comparative Example 1
[0041] The SiO2 wet gel is dried to obtain a highly dispersed and strong low-temperature flexible white carbon black for reinforcing green tires.
[0042] Comparative Example 2
[0043] 500g SiO2 wet gel was added to the reactor, 250g deionized water was added, and the mixture was heated to 80°C with stirring in an oil bath, the modified pH was adjusted to 3.5, and 70g of pre-hydrolyzed PTMS (the hydrolysis conditions were the same as those in Example 1) was added for modification, and the reaction time was 90min. After the reaction was completed, the mixture was washed with alcohol, filtered, and dried to obtain a highly dispersed and strong low-temperature flexible white carbon black for reinforcing green tires.
[0044] Comparative Example 3
[0045] 500g SiO2 wet gel was added to the reactor, 250g deionized water was added, and the mixture was stirred and heated to 90°C in an oil bath, the modified pH was adjusted to 3.5, and 70g pre-hydrolyzed A171 (the hydrolysis conditions were the same as those in Example 1) was added for modification, and the reaction time was 90min. After the reaction was completed, the mixture was washed with alcohol, filtered, and dried to obtain a highly dispersed and strong low-temperature flexible white carbon black for reinforcing green tires.
[0046] Comparative Example 4
[0047] 500g SiO2 wet gel was added to the reactor, 250g deionized water was added, and the mixture was heated to 80℃ with stirring in an oil bath, and the modified pH was adjusted to 3.5. Then, pre-hydrolyzed PTMS and A171 (PTMS mass was 50g, A171 mass was 20g, ethanol and water were 140g and 50g respectively, and the hydrolysis pH value was 4.0) were added. The total mass of the modifier was 70g, and the mass ratio of PTMS: A171 was 5:2 for modification. The reaction time was 90min. After the reaction was completed, the mixture was washed with alcohol, filtered and dried to obtain a highly dispersed and strong low-temperature flexible white carbon black for reinforcing green tires.
[0048] The test methods for each performance parameter are as follows:
[0049] (1) Determination of activation degree:
[0050] 50 mL of distilled water was placed in a 100 mL beaker, 1.0 g of white carbon black was added, stirred for 30 min and then allowed to stand for 24 h. The white carbon black that sank to the bottom was separated, dried and weighed, and the activation degree was calculated according to the following formula:
[0051]
[0052] (2) Determination of lipophilicity:
[0053] Measure 50 mL of distilled water and place it in a 100 mL beaker, add 1.0 g of white carbon black, and use anhydrous ethanol titration method to soak the powder until it is completely sunk in the water phase. Record the amount of anhydrous ethanol added V (mL) at this time, and then calculate the lipophilicity according to the following formula:
[0054]
[0055] (3) Determination of hydroxyl content:
[0056] This study follows the specific determination steps of T / FSI 049-2020 to determine the number of surface hydroxyl groups of modified silica. Weigh 2.0 g of silica in a 200 mL beaker, add 25 mL of anhydrous ethanol, and then add 75 mL of 20% NaCl solution. After magnetic stirring, add 0.1 mol / L NaOH (or 0.1 mol / L HCl) standard solution to adjust the pH of the test solution to 4, and then slowly add 0.1 mol / L NaOH to adjust the pH to 9, and keep the pH unchanged for 20 s. The number of hydroxyl groups (N) on the surface of each square nanometer of silica is calculated according to the formula:
[0057]
[0058] N A : Avogadro's constant
[0059] C: The exact concentration of NaOH standard solution (mol / L)
[0060] V: The volume consumed by adding 0.1 mol / L NaOH to change the pH value of the solution from 4 to 9 (mL)
[0061] M: mass of white carbon (g).
[0062] S: Specific surface area of the sample (nm 2 / g)
[0063] (4) Preparation and vulcanization of rubber mix:
[0064] According to HG / T2404-2020 "Identification of precipitated hydrated silica in styrene-butadiene rubber", the rubber was mixed with the following formula: 200g styrene-butadiene rubber, 100g silica, 10g ZnO, 2g stearic acid, 6g polyethylene glycol, 2.4g accelerator DM, 1.4g accelerator M, 1g accelerator DPG, and 4g sulfur. The silica-styrene-butadiene rubber mixture was then vulcanized at 160°C on a flat vulcanizer.
[0065] (5) Performance determination of rubber mix:
[0066] The Mooney viscosity of rubber was tested according to GB / T1232 "Determination of unvulcanized rubber by disc shear viscometer - Part 1: Determination of Mooney viscosity".
[0067] The vulcanization characteristics of rubber were tested according to GB / T9869-1997 “Determination of vulcanization characteristics of rubber compounds (disc oscillation vulcanizer method)”.
[0068] The stress-strain characteristics test is carried out according to GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber".
[0069] The performance of the mixed rubber was tested using an RPA rubber processing analyzer. The strain scanning conditions were: frequency 1 Hz, temperature 70 °C, and strain range 0.1% to 100%.
[0070] The RPA rubber processing analyzer was used to scan the temperature of the mixed rubber to test the dynamic performance changes of the rubber. The scanning conditions were: strain 0.25%, frequency 10 Hz, and temperature range -20℃~70℃.
[0071] The performance of the white carbon black obtained in the above examples and comparative examples was tested, and the test results are shown in Table 1.
[0072] Table 1 Performance test table of white carbon black in various embodiments and comparative examples
[0073]
[0074] The rubber refining performance of the white carbon black in Examples 1-5 and Comparative Examples 1-4 in the above examples was tested, and the test results are shown in Table 2.
[0075] Table 2 White carbon black rubber refining performance test table of each embodiment and comparative example
[0076]
[0077] From Examples 1-5 and Comparative Examples 1-4, it can be seen that the number of surface hydroxyl groups of the white carbon black provided by the present invention is reduced, the activation degree and lipophilicity are significantly improved, and thus the hydrophobicity is enhanced, solving the problem of poor dispersibility of white carbon black in the rubber matrix. The activation degree reaches 100%, the lipophilicity reaches 10.1%, and the number of surface hydroxyl groups is reduced to 0.924 / nm 2 .
[0078] When applied to styrene-butadiene rubber, compared with unmodified silica / SBR, due to the grafting of benzene rings and unsaturated double bonds on the surface, the benzene rings have greater steric hindrance and require greater van der Waals forces to make the molecules slip, while the unsaturated double bonds can participate in the vulcanization of the rubber. The two work together to increase the crosslinking density of the rubber, thereby increasing the reinforcing effect of silica, and at the same time, it is better than the effect of single modifier modification. The vulcanization time is reduced by 68.8%, the Mooney viscosity is reduced by 61.3%, and the processing difficulty is reduced; the tensile strength is increased by 14.0%, the elongation at break is increased by 11.3%, and the 300% and 500% elongation stresses are increased by 43.4% and 31.3% respectively, which improves the mechanical strength.
[0079] After the white carbon black of Example 1 and Comparative Examples 1, 2, and 3 were applied to styrene-butadiene rubber, the dynamic mechanical properties of the rubber were tested using a rubber processing analyzer. The test data are shown in Table 3.
[0080] Table 3 Dynamic mechanical properties of the rubber materials of Example 1 and the comparative examples
[0081]
[0082] From the data in the analysis table, it can be seen that the dynamic mechanical properties of the composite modified product in Example 1 are improved compared with the unmodified silica / SBR and the single modifier silica / SBR. Among them, the Payne effect of the PTMS+A171 modified silica / SBR is greatly weakened compared with the unmodified silica / SBR, and △G′ decreases by 88.7%. Its dispersibility in the rubber matrix is greatly improved, tanδ(-10℃) increases by 94.6%, tanδ(0℃) increases by 112.0%, and the shear compliance is greatly improved across the board, among which the shear compliance (0℃) increases by 149.2%, the shear compliance (-10℃) increases by 150.0%, and the shear compliance (30℃) increases by 162.5%. The above data fully demonstrate that the PTMS+A171 modified silica / SBR of the present invention has improved dispersibility in the rubber material compared with the unmodified silica / SBR, and obtains greater viscosity resistance and traction in a normal low temperature environment, thereby improving the low-temperature flexibility of the tread rubber.
[0083] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing white carbon black, characterized in that: The method comprises the following steps: adding silicon dioxide wet gel, deionized water and vinyl trimethoxysilane into a reaction kettle, stirring and heating to 70-90 DEG C; adjusting the modified pH to 2.5-4.5, adding phenyl trimethoxysilane pre-hydrolysis liquid, heating to 70-90 DEG C for modification reaction, and washing with alcohol, filtering and drying after the reaction is completed to obtain white carbon black.
2. The method for preparing white carbon black according to claim 1, characterized in that: The mass ratio of vinyl trimethoxysilane to phenyl trimethoxysilane in the phenyl trimethoxysilane pre-hydrolyzate is 5:
2.
3. The method for preparing white carbon black according to claim 1, characterized in that: The total mass of the vinyl trimethoxysilane and the phenyl trimethoxysilane is 3.5%-17.5% of the mass of the silicon dioxide wet gel.
4. The method for preparing white carbon black according to claim 3, characterized in that: The total mass of the vinyl trimethoxysilane and the phenyl trimethoxysilane is 14%-17.5% of the mass of the silicon dioxide wet gel.
5. The method for preparing white carbon black according to claim 1, characterized in that: The PTMS pre-hydrolysis solution is prepared by the following method: PTMS is hydrolyzed in a solvent of anhydrous ethanol and water, the hydrolysis pH is 4.0, and the mass ratio of PTMS to anhydrous ethanol and water is 5:14:
5.
6. The method for preparing white carbon black according to claim 1, characterized in that: The modified pH is 3.
5.
7. The method for preparing white carbon black according to claim 1, characterized in that: The modification reaction time is 30-150 min.
8. The method for preparing white carbon black according to claim 7, characterized in that: The modification reaction time is 90 min.
9. White carbon black prepared by the method according to any one of claims 1 to 8.
10. Use of the white carbon black according to claim 9 in reinforcing green tires.
Citation Information
Patent Citations
Surface modified silicon dioxide particles
CN102027074A
Preparation method of modified fumed silica for LED packaging reinforcement
CN102504613A
Preparation method of hydrophobic high-reinforcing white carbon black
CN107337810A
Preparation method of hydrophobic high-wear-resistance white carbon black
CN110054914A
Preparation method of high-abrasion-resistant white carbon black for reinforcement of butadiene styrene rubber
CN110387145A